Gospodarski važni virusi jezgričavog voća - Ivić, Dario (2019)
Virusi jabuke, kruške ili dunje relativno su slabo poznati stručnjacima i voćarima. Najvažnijim virusima koji se javljaju na jezgričavim voćnim vrstama smatraju se virus mozaika jabuke (Apple mosaic virus, ApMV), virus klorotične pjegavosti lista jabuke (Apple chlorotic leaf spot virus, ACLSV), virus brazdavosti debla jabuke (Apple stem grooving virus, ASGV) i virus jamičavosti debla jabuke (Apple stem pitting virus,ASPV). U radu je ukratko opisana njihova važnost, biologija i regulativni status, kao i osnovne mjere zaštite.
Virus diseases of apple, pear and quince are relatively less known to agricultural experts and fruit producers. Apple mosaic virus (ApMV), Apple chlorotic leaf spot virus (ACLSV), Apple stem grooving virus (ASGV) and Apple stem pitting virus (ASPV) are usually considered economically most important viruses of pome fruit. Their significance, biology and regulatory status are briefly described, as well as basic control measures.
Bibliografija: str. 132-136.
Sažetak ; Abstract.
Keywords: Jezgričavo voće -- Jabuka -- Kruška -- Dunja -- Virusi